Affirmative Career Counselling with Transgender and Gender Nonconforming Clients: A Social Justice Perspective - Wada, Kaori; McGroarty, Eleanor J.; Tomaro, Jann; Amundsen-Dainow, Evie (Canadian Journal of Counselling and Psychotherapy, 2019)
The ongoing lack of scholarly attention to, and limited counsellor competence in, career counselling with transgender and gender nonconforming (TGNC) individuals contributes to perpetuating the marginalization of these populations. The career-related challenges and disparity in career outcomes of TGNC populations have been documented. This article takes a social justice orientation to stir a transformation from within the field of career counselling. We first critically examine the applicability of career theories with TGNC clients, and review the strengths and limitations of the following three theories: Super’s developmental theory, Gottfredson’s theory of circumscription and compromise, and social cognitive career theory. We then propose an affirmative career counselling model, which (a) takes gender and intersectionality into account throughout the career counselling process, and (b) effectively integrates contemporary theories that address systemic factors. The article concludes with suggestions for future research, highlighting the need for collaborative, participatory research that leads to social change.